The influence of market wages and parental history on child labour and schooling in Egypt - Jackline Wahba (Institute for the Study of Labor (IZA), 2005)
This paper examines the influence of adult market wages and having parents who were child labourers on child labour, when this decision is jointly determined with child schooling, using data from Egypt. The empirical results suggest that low adult market wages are key determinants of child labour; a 10 percent increase in the illiterate male market wage decreases the probability of child labour by 22 percent for boys and 13 percent for girls. The findings also indicate the importance of social norms in the inter-generational persistence of child labour: parents who were child labourers themselves are on average 10 percent more likely to send their children to work. In addition, higher local regional income inequality increases the likelihood of child labour.
Keywords: J13; J20; O15; 330; child labour; child schooling; wages; Lohnniveau; Kinderarbeit; Bildungsverhalten; Ägypten